Pengaruh Kompetensi, Organizational Citizenship Behavior Dan Budaya Organisasi Terhadap Kepuasan Kerja Dan Kinerja Tenaga Perawat Pada Rumah Sakit Islam Boyolali - Ifah Lathifah; Sunardi Sunardi (ProBank, 2025)
The purpose of this study was to determine, test and analyze the significance of the influence of competence, organizational citizenship behavior and organizational culture on job satisfaction and performance of nurses at the Boyolali Islamic Hospital. Data collection technique with questionnaires. The sample took 100% of the population with a census technique, namely 87 respondents. Data analysis with instrument testing, linearity testing, hypothesis testing, and path analysis. The results of the t-test equation 1 and equation 2 prove that: OCB and organizational culture have a significant effect on job satisfaction but competence has no significant effect on job satisfaction; Competence, OCB and job satisfaction have a significant effect on performance but organizational culture has no significant effect on performance. The results of the calculated F value prove that together competence, OCB, organizational culture and job satisfaction have a significant effect on performance. The results of the total determination value (R2) of 0.956 mean that performance is explained by competence, OCB, organizational culture and job satisfaction by 95.6% and the remaining 4.4% is explained by other factors. The results of the path analysis obtained that to improve performance with a direct path of competence to performance which is the most dominant and most effective path. The intervening variable of job satisfaction effectively mediates the influence of organizational culture on performance but is not effective in mediating the influence of competence on performance and OCB on performance